Patient Experience with Side Effects of Chemotherapy Drugs in Hospital Oncology Installations - Nur Ela; Siti Ainul Kholipah; Abi Surya Wijaya (Al Makki Publisher, 2025)
Cancer is one of the leading causes of death in the world, with an ever-increasing incidence. Based on GLOBOCAN 2022 data, more than 20 million new cases of cancer and 9.7 million deaths were recorded globally, with a projected increase of up to 28.4 million cases by 2040. This study aims to explore and describe the subjective experience of patients in dealing with chemotherapy side effects in the Oncology Installation of Hospital X. The method used is a qualitative research with a descriptive phenomenological design, involving 15 patients who meet the inclusion criteria. Data were collected through in-depth interviews, participatory observations, and semi-structured questionnaires. The results showed that nausea and vomiting were the most common side effects (93%, severity score 7.8), followed by fatigue (87%, 8.2) and hair loss (80%, 6.5). Family support has been shown to affect patients' ability to manage symptoms, while limited pre-chemotherapy education and the number of clinical pharmacists are barriers to treatment. In conclusion, the treatment of chemotherapy patients requires a holistic approach based on patient-centered care that integrates physical, psychological, and social aspects, as well as strengthening education and clinical pharmacy services to improve the patient's quality of life during therapy.